The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.2169/internalmedicine.1239-18
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary <i>Scedosporium apiospermum</i> Infection with Pulmonary Tumorlet in an Immunocompetent Patient

Abstract: Scedosporium apiospermum is an opportunistic fungus that can cause various types of infections, including localized infections and life-threatening disseminated infections, particularly in immunocompromised patients. Treatment is especially challenging due to its multidrug resistance. We herein report the case of a 73-year-old woman who was non-immunocompromised but developed S. apiospermum lung infection and a pulmonary tumorlet. To our knowledge, this is the first report of the coexistence of pulmonary S. ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Antifungal minimum inhibitory concentrations were measured in 6 reports. [20,22,24,27,30,33] Four cases reported drug-related side-effect attributed to miconazole and voriconazole, leading to the discontinuation of treatment. [8,22,34,35]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antifungal minimum inhibitory concentrations were measured in 6 reports. [20,22,24,27,30,33] Four cases reported drug-related side-effect attributed to miconazole and voriconazole, leading to the discontinuation of treatment. [8,22,34,35]…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is worth to notice that a 5-year follow-up was conducted in 2 cases in our study. [27,29] One case reported a 73-year-old woman who developed S apiospermum lung infection and a pulmonary tumorlet. [29] The other case reported a 40-year-old woman who had right lower cystic bronchiectasis and S apiospermum colonization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. apiospermum infection is di cult to treat as it has been reported to be resistant to many antifungal agents, such as uconazole, ketoconazole, ucytosine, terbina ne, itraconazole, and liposomal amphotericin B. Nevertheless, it is susceptible to voriconazole, and a few studies have reported its e cacy in the treatment of S. apiospermum infection [5,12,13,15]. According to the literature, surgical resection is an effective treatment for localized lesions, and even in immunocompetent individuals, the infection usually necessitates complete surgical resection [1].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on the PET-CT report, it is suggested that the local metabolic activity of the upper lobe of the right lung was increased (SUVmax =2.8), and peripheral gonadal carcinoma was suspected; 2. after antifungal treatment, the foci were not signi cantly absorbed, and the possibility of pulmonary fungal infection complicated with lung cancer could not be excluded. This surgery aimed to remove the foci and actively resect the pulmonary tumor simultaneously based on a reported case of pulmonary S. apiospermum infection with pulmonary tumorlets in an immunocompetent patient [15]. The patient was followed up for 10 months after surgery, and the therapeutic effect was effective.…”
Section: Literature Reviewmentioning
confidence: 99%